2023
DOI: 10.1002/mdc3.13774
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Social Avoidance in Adults with Essential Tremor

Abstract: BackgroundPeople with essential tremor (ET) can be subject to stigma, and some adopt avoidance behaviors. Characteristics associated with ET stigma and the relationship between perceived stigma and social dysfunction have not been studied.ObjectivesTo discern predictors of perceived stigma and social dysfunction in ET, and to identify potentially treatable psychological factors associated with social dysfunction.MethodsWe surveyed ET patients (n = 158) on recalled stigma incidents and social dysfunction relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This is particularly relevant, as psychometric evaluations could reveal underlying psychological factors that might not be immediately apparent through physical examinations alone [19][20][21][22]. The significant psychometric differences identified underline the necessity of incorporating comprehensive psychological assessments into the diagnostic process for tremors, potentially enhancing the accuracy of distinguishing between ET and FT [23][24][25]. By integrating detailed psychometric evaluations into the routine assessment of patients with tremors, clinicians could better understand the patient's condition, which is crucial for effective treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant, as psychometric evaluations could reveal underlying psychological factors that might not be immediately apparent through physical examinations alone [19][20][21][22]. The significant psychometric differences identified underline the necessity of incorporating comprehensive psychological assessments into the diagnostic process for tremors, potentially enhancing the accuracy of distinguishing between ET and FT [23][24][25]. By integrating detailed psychometric evaluations into the routine assessment of patients with tremors, clinicians could better understand the patient's condition, which is crucial for effective treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…Findings were categorized under prevalence statistics (29 studies),[ 15 16 17 18 19 20 21 22 23 ] proposed pathophysiologic mechanisms (15 studies),[ 4 5 6 7 24 25 26 27 28 29 30 ] assessments of psychiatric comorbidities (nine studies),[ 31 32 33 34 35 36 37 38 39 40 ] the stigma associated with tremor disorder (two studies),[ 41 42 ] and evaluations of quality-of-life impact (five studies). [ 36 43 44 45 46 ]…”
Section: R Esultsmentioning
confidence: 99%
“…[ 41 ] Assessments of stigma dimensions revealed that ET patients frequently conceal their diagnosis and feel uncomfortable in social situations due to their tremors. [ 42 ] However, no studies have comprehensively evaluated various dimensions of stigma and associated determinants, specifically among Indian patients with tremor disorders.…”
Section: R Esultsmentioning
confidence: 99%